Odpowiedzi

2010-02-21T13:59:23+01:00
2 ( x+y ) - (x-y) = 4
3 (x - 2y) + 4 (x+y)= 5

2x+2y - x +y = 4
3x - 6y + 4x +4y = 5

x + 3y = 4
7x - 2y = 5

x = 4 - 3y
7(4-3y) - 2y = 5

28 - 23y = 5
- 23 y = - 23
y = 1

x = 4 - 3 x 1
x = 1


y=1
x=1
____________________________

4 (x+ 2y) - 3(x-y) = 42
2(y-x) +3 (x-y) = -6

4x + 8y - 3x + 3y = 42
2y - 2x +3x - 3y = -6

x + 11y = 42
x - y = -6 /x(-1)

x + 11y = 42
-x +y = 6

12 y = 48
y = 4

x = -2
y = 4

______________________

3 (x+y)- 2 (x- 2y ) =5
2(x + 2) - 4(y+1)= -8

3x + 3y - 2x + 4y = 5
2x + 4 - 4y - 4 = -8

x + 7y = 5
2x - 4y = -8

x = 5 - 7y
2(5 - 7y) - 4y = -8

10 - 14 y - 4 y = -8

10 - 18 y = -8

-18y = -18
y=1

x = 5 - 7
x = -2

x=-2
y=1
2010-02-21T14:01:01+01:00
2(x+y) -(x-y) = 4
3(x-2y) +4(x+y) =5

2x+2y-x+y=4
3x-6y+4x+4y=5

x+3y=4
7x-2y=5

x=-3y+4
7x-2y=5

x=-3y+4
7(-3y+4) - 2y=5

x=-3y+4
-21y+28-2y=5

x=-3y+4
-23y=-23 | /(-23)

x=-3y+4
y=1

x=-3*1 +4
y=1

x=1
y=1

















  • Użytkownik Zadane
2010-02-21T14:03:42+01:00
A)
2 ( x+y ) - (x-y) = 4
3 (x - 2y) + 4 (x+y)= 5

2x+2y-x+y=4
3x-6y+4x+4y=5

x+3y=4 /*(-7)
7x-2y=5

-7x-21y=-28
7x-2y=5
__________
-23y=-23
y=1

x+3*1=4
x+3=4

x=1
y=1


b) 4 (x+ 2y) - 3(x-y) = 42
2(y-x) +3 (x-y) = -6

4x+8y-3x+y=42
2y-2x+3x-3y=-6

x+9y=42
x-y=-6

-x-9y=-42
x-y=-6
________
-10y=-48
y=4,8

x-4,8=-6
x=-1,2

x=-1,2
y=4,8

c) 3 (x+y)- 2 (x- 2y ) =5
2(x + 2) - 4(y+1)= -8

3x+3y-2x+4y=5
2x+4-4y-4=-8

x+7y=5 /*(-2)
2x-4y=-8

-2x-14y=-10
2x-4y=-8
__________
-18y=-18
y=1

x+7*1=5
x+7=5
x=-2

x=-2
y=1